The relationship between reward management and job satisfaction at Pejabat Pendidikan Daerah Gombak (PPDG) / Nurufatihah Mohamad Nasir - Mohamad Nasir, Nurufatihah (Faculty of Business and Management, 2017)
Reward management include of financial rewards and non-financial reward. Human resource management should know with selecting the right rewards for employees to increase employee’s job satisfaction. Many organizations are unable to identify the types of rewards which are best used to retain of employee’s. This study was conducted to determine the relationship between rewards and job satisfaction as well as to identify the types of rewards that have the strongest effect employee’s job satisfaction. Financial rewards such as base salary raise, salary increment, overtime payment, pension schemes, and bonuses have been discussed in this research. While, non-financial rewards consist of recognition, formal appreciation letter, informal praise, feedback and support, internal training program, and office equipment also have been discussed in this research. Besides that, this research target of population is the employees working in Pejabat Pendidikan Daerah Gombak (PPDG). The population size of respondent in the area that will study is 104 respondents including male and female. However, since the population of PPD Gombak is only 104, researcher decided to distribute to all 104 employees for reliable results. 104 questionnaires were distributed and 104 were collected for analysis. The sample was selected through simple random sampling techniques. Primary data was collected through the use of questionnaires. In addition, two hypotheses were assumed and had been tested in this research. The data was analyzed using Pearson Correlation analysis and Multiple Regression analysis. From the results of Pearson Correlation Analysis, rewards are positively and significantly associated job satisfaction. For financial rewards (r = 0.980) while non-financial rewards (r = 0.503). Thus, hypothesis 1 and hypothesis 2 were supported. Moreover, the regression results has indicated that financial rewards (β = 0.974) has a stronger impact on job satisfaction as compared to non-financial rewards (β = 0.012). Further conclusion of the results and recommendations for future research are presented in the study.